2015
DOI: 10.3109/0886022x.2015.1088335
|View full text |Cite
|
Sign up to set email alerts
|

Central hemodynamics, vascular stiffness, and nocturia in patients with type 2 diabetes

Abstract: Recently, studies have shown that the presence of nocturia may not be a benign condition and related with systemic illness and mortality. Elevated blood pressure (BP) was another factor related with nocturia. Type 2 diabetes mellitus (T2DM) is also associated with nocturia. It is now clear that, apart from peripheral BP, central hemodynamic parameters are important for cardiovascular prognosis. However, no previous study in the literature examined the relationship between nocturia and central hemodynamic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Furthermore, hypertension has been suggested to be related to defects in the nitric-oxide pathway that alter pressure-natriuresis and sodium retention and cause compensatory nocturnal polyuria 29 . Additionally, central haemodynamic parameters, such as central blood pressure, cardiac output, pulse wave velocity and vascular stiffness, have been suggested to be associated with nocturia 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hypertension has been suggested to be related to defects in the nitric-oxide pathway that alter pressure-natriuresis and sodium retention and cause compensatory nocturnal polyuria 29 . Additionally, central haemodynamic parameters, such as central blood pressure, cardiac output, pulse wave velocity and vascular stiffness, have been suggested to be associated with nocturia 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with T2DM, age, creatinine clearance, and augmentation index (24 hours) were independently associated with nocturia frequency (linear regression analysis), and nocturia was associated with 24-hour creatinine clearance, hemoglobin, fasting blood glucose, and PWV (24 hours) (logistic regression analysis). 36 Hemodynamic parameters were seen to differ between patients with and without nocturia, and in patients with T2DM, nocturia was associated with central hemodynamic and arterial stiffness parameters including PWV and augmentation index. 36 Therefore, nocturia appears to reflect vascular injury resulting in increased arterial stiffness as well as hyperglycemia in patients with T2DM.…”
Section: Association Between Arteriopathy and Nocturiamentioning
confidence: 90%
“…36 Hemodynamic parameters were seen to differ between patients with and without nocturia, and in patients with T2DM, nocturia was associated with central hemodynamic and arterial stiffness parameters including PWV and augmentation index. 36 Therefore, nocturia appears to reflect vascular injury resulting in increased arterial stiffness as well as hyperglycemia in patients with T2DM. These findings are supported by another study of 303 Japanese men with late-onset hypogonadism, in which nocturia was found to be associated with a higher brachial-ankle PWV on a multivariate linear regression model after adjustment for serum triglycerides, fasting blood sugar, and total testosterone.…”
Section: Association Between Arteriopathy and Nocturiamentioning
confidence: 90%
See 2 more Smart Citations